Quantifying music genius, or Handel on the balance: A scale of musical merit from 1776 - Ilias Chrissochoidis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2016)
The December 1776 issue of the "Gentleman's Magazine," flagship of British periodicals, features an item unique in the history of 18th-century music: the "Scale to Measure the Merits of Musicians." It comprises an evaluative chart of two-dozen composers, marking the first quantitative assessment of musical skill. This paper explicates the chart's structure and content, traces its methodology to the founder of modern art criticism Roger de Piles, proposes Charles Burney as its likely author, and places it in the context of a rising music historiography in Britain.
Keywords: 330; Music; quantification; Handel; Roger de Piles